Civilising Mission or Colonial Experiment? Unmasking the Dutch Ethical Policy in Indonesia - Dwi Prasetyo; Muhammad Amiruddin Salleh; Youssef Al-Fayez; Thomas van Leeuwen (Senarai: Journal of Islamic Heritage and Civilization, 2025)
Debates in colonial and postcolonial scholarship continue to grapple with the question of whether colonial rule laid the foundations for the subsequent development of formerly colonised nations. Although many postcolonial critics have dismissed this notion, the Dutch colonial experience in Indonesia, particularly in Aceh, has not been sufficiently integrated into this wider debate. Scholarly consensus suggests that the Dutch Ethical Policy was not a purely humanitarian project but rather a response to chronic administrative inefficiency, influenced heavily by the Dutch military and political occupation of Aceh between 1873 and 1942. Since Aceh served as the testing ground for this policy, the present study examines its efficiency, role, and broader implications for Acehnese society. Building upon ethnological studies and the political advice of Christiaan Snouck Hurgronje (1857–1936), the Ethical Policy is best understood as a hybrid of conciliation and coercion, an authoritarian strategy intended to reinforce colonial dominance. Findings indicate that Acehnese elites who aligned themselves with Dutch authority were co-opted into promoting the so-called enlightenment mission, while those who resisted faced systematic surveillance, repression, and military violence. Moreover, the educational and infrastructural reforms initiated under this policy produced new social stratifications, where access to privilege and networks was increasingly unequal. Employing a qualitative methodology, this study analyses colonial newspapers, government reports, and official correspondence to illuminate the contested legacy of the Ethical Policy. It is anticipated that these findings will contribute a nuanced perspective to the study of modern civilization in both Aceh and Indonesia.